Pendekatan Edukasi dan Pelatihan dalam Upaya Mengatasi Tantangan Pembangunan Berkelanjutan di Nagari Ampek Koto Palembayan - Haiyyu Darman Moenir; Maryam Jamilah; Muhammad Farhan; Fatimah Azzahra (Warta Pengabdian Andalas, 2024)
Nagari Ampek Koto Palembayan has a wealth of natural resources due to its fertile soil and favorable topography. However, with the existing potential, Nagari Ampek Koto Palembayan faces challenges in achieving sustainable development targets, especially in health, animal husbandry, plantations, and the economy. Health problems related to stunting in children, limited animal feed in the livestock sector, pathogen infections that attack banana plants in the plantation sector, and the low price of palm sugar in the economic sector are the main obstacles to improving community welfare. As a form of empowerment, the research team conducted a series of interventions designed to increase community awareness and knowledge on these issues. Socialization and education on nutrition for mothers of toddlers were conducted to reduce stunting rates, training on making animal feed based on agricultural waste aimed at increasing feed availability, and lectures on how to prevent pathogen infections in banana plants aimed at maintaining the sustainability of the plantation sector. In addition, the community was also trained to process palm sugar into a higher value-added product, namely ant sugar. The results of these activities showed an increased understanding of the importance of nutrition for children to prevent stunting and an understanding of agricultural waste management and ant sugar production, which also encouraged the community to utilize existing resources optimally.